Are we Baby Boomers, Gen X and Gen Y? A qualitative inquiry into generation cohorts in Malaysia - Ting, Hiram; Tze Yin, Lim; De Run, Ernest Cyri; Koh, Hannah; Murni, Sahdan (Kasetsart University, 2018)
Notwithstanding the prevalent use of generation labels and descriptions from U.S. sources in the marketing literature and segmentation practices in Malaysia, there is an extreme lack of studies that justify such adoption with theoretical support and empirical evidence. The present study was performed to explore generation cohorts in Malaysia using sociological theories of generations as the underpinning basis. The purpose was to identify the major external events which have impacted Malaysians during their formative years and to define actual generation cohorts in the Malaysian context. A qualitative approach via personal interview was administered and 80 nationwide interviews were conducted and audio-recorded. The data were then transcribed and analyzed using content analysis with the aid of the ATLAS.ti software. The findings suggested that the experiences of external events which Malaysians have are different from the experiences of the U.S. population. As such, five generation cohorts were proposed based on the collective experience of the events which transpired during the formative years respectively. The study not only unearthed actual Malaysian generation cohorts, it can also pioneer future investigation pertaining to generation cohorts in Malaysia and the use of generations in various studies and practices. © 2017 Kasetsart University